HASRAT MANUSIA MENUJU TUHAN DALAM NOVEL ḤAYY BIN YAQẒAN KARYA IBN ṬUFAYL - Iftitah, Iftitah (Living Islam: Journal of Islamic Discourses, 2020)
This study discusses the development of human desires in Ḥayy bin Yaqẓan by Ibn Ṭufayl. Humans are classified as creatures that are very dynamic in realizing their lives rather than animals that tend to be static, so humans are considered as the most perfect creatures. But, behind this perfection, humans experience turmoil in facing a desire that always develops even beyond all needs. This research is a literature study using Jacques Lacan’s psychoanalytic approach as a data analysis tool. This research concludes that the stages of human development begin with a void of identity, self-identification, and understanding of the essence of self and life. In the context of psychology theory, the development of desires will never reach full fulfillment, because the desires that arise continue to experience the development of the extent to which the desire exceeds the object of his desire. However, in the context of this research, the fulfillment of needs will end when a person comes to the position of his knowledge of the essence of live and life. He will realize that the desire in him, is the desire to recognize the essence of the God that is in them.